Analisis Ijaz Dalam Ilmu Balaghah Pada Al-Baqarah Ayat: 285: Kewajiban Beriman Kepada Allah - Dicky Syahfrizal; Aziz Israq (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Al-Quran Surah Al-Baqarah 285: this research aims to apply the values ​​of faith in the daily lives of Muslims.